The Role of Sabhara Two-Wheel Patrol in Reducing Thefts - Karisoh, Priscillia Putri Loewensky (Police Studies Review, 2024)
Traffic violations in Majalengka Regency are dominated by students. Conducting research with the aim to find and analyze the causes of undisciplined student traffic behavior, the constraints experienced by Dikyasa Unit in preventing undisciplined student traffic behavior through the Police Goes To School program and the Dikyasa Unit's efforts in preventing undisciplined student traffic behavior through the Police program Go to school. This study uses Theory of Reasoned Action, Communication Theory and Management Theory, while the concepts used include the Concept of Efforts, Preventing Concepts, the Concept of Traffic Discipline, Student Concepts, Concepts of Unified Unit and the Concept of Police Goes to School. Using a qualitative approach with field research methods. The research focus is on the efforts of Dikyasa Unit through the Police Goes To School Program. Data collection techniques by means of observation, interviews, and document studies. Research location in the Majalengka District Police jurisdiction. Data validity uses triangulation of time, techniques and sources. Data Analysis Techniques using data reduction, data presentation and drawing conclusions. The results showed students did not discipline the behavior due to intentions and subjective norms due to lack of knowledge from students. Dikyasa Unit personnel have not entirely followed the education and education department education, the delivery of monotonous messages and no supervision after the implementation of the Police Goes To School becomes an obstacle. Efforts carried out by the Dikyasa Unit are to provide guidance on PKS, Saka Bhayangkara, the United Nations, Lantas Gymnastics and the socialization of traffic regulations. The conclusion of this research is the undisciplined behavior of student traffic caused by the intention to gain benefits, subjective norms and lack of knowledge possessed, constraints experienced by personnel, lack of variation in the delivery of messages, and lack of supervision of the target. Suggestions from the author, among others (1) it is necessary to regulate traffic around the school, (2) need to enforce rules by the school, (3) the need to propose members to implement Dikjur and (4) the need to insert material using videos and brochures.